Unearthing global financial inclusion levels and analysis of financial inclusion as a mediating factor in global human development - Unnikrishnan, Roshny; Jagannathan, Lakshmi (Serbian Journal of Management, 2014)
This study is a result of the author’s inquisition to unearth the current values of Global Financial Inclusion and its relationship with economic growth measured by Gross Domestic product(GDP) and human development measured by United Nations Human Development Index(HDI).The Financial Inclusion (FI) levels are measured using Index for Financial Inclusion .The relationship between GDP and HDI with FI as mediator is validated for on a global level based on relevant data adopting methodology adopted from previous mediation analysis and studies. An overall global mediation analysis is undertaken to establish Financial Inclusion as a mediating factor and partial mediation on human development is validated. Key words: Gross Domestic product (GDP), Financial Inclusion (FI), Human Development Index (HDI), Mediation Analysis, Multiple Regression Analysis,